Editorial - Monroy Flores, Verel Elvira (Cooperativismo & Desarrollo, 2017)
This issue of Cooperativismo & Desarrollo (c&d) shows a variety of perspectives on heartfelt matters such as the environment, ancestral knowledge linked to territorial experience, social and economic participation of social and solidarity organizations, and other topics related to productivity in the country and food sovereignty, going through business competitiveness and higher education and its impact on the environment.